Extracellular vesicles of Trypanosoma cruzi tissue-culture cell-derived trypomastigotes: Induction of physiological changes in non-parasitized culture cells - Retana Moreira, Lissette (2019)
Background: Trypanosoma cruzi is the obligate intracellular parasite that causes Chagas disease. The pathogenesis of this disease is a multifactorial complex process that involves a large number of molecules and particles, including the extracellular vesicles. The presence of EVs of T. cruzi was first described in 1979 and, since then, research regarding these particles has been increasing. Some of the functions described for these EVs include the increase in heart parasitism and the immunomodulation and evasion of the host immune response. Also, EVs may be involved in parasite adhesion to host cells and host cell invasion. Methodology/Principal findings: EVs (exosomes) of the Pan4 strain of T. cruzi were isolated by differential centrifugation, and measured and quantified by TEM, NTA and DLS. The effect of EVs in increasing the parasitization of Vero cells was evaluated and the ED50 was calculated. Changes in cell permeability induced by EVs were evaluated in Vero and HL-1 cardiomyocyte cells using cell viability techniques such as trypan blue and MTT assays, and by confocal microscopy. The intracellular mobilization of Ca2+ and the disruption of the actin cytoskeleton induced by EVs over Vero cells were followed-up in time using confocal microscopy. To evaluate the effect of EVs over the cell cycle, cell cycle analyses using flow cytometry and Western blotting of the phosphorylated and non-phosphorylated protein of Retinoblastoma were performed. Conclusion/Significance: The incubation of cells with EVs of trypomastigotes of the Pan4 strain of T. cruzi induce a number of changes in the host cells that include a change in cell permeability and higher intracellular levels of Ca2+ that can alter the dynamics of the actin cytoskeleton and arrest in the cell cycle at G0/G1 prior to the DNA synthesis necessary to complete mitosis. These changes aid the invasion of host cells and augment the percentage of cell parasitization.